Prevalence of stress and burnout among information technology professionals during COVID-19 pandemic due to work from home situation - Padmashali, Ashwini (International Journal Of Community Medicine And Public Health, 2023)
Background: To prevent the transmission of COVID-19 infection, lockdown and social distancing was imposed across various countries. The people working in the information technology (IT) sector started working remotely. The aim of this study was to determine the prevalence of stress and burnout among the IT professionals due to sudden transition to work from home situation. Methods: In the present cross-sectional study an online questionnaire was used for data collection from the software professionals who worked from home for a minimum duration of 1 year during the pandemic. The study sample was collected using convenience sampling and sample size attained was 40. The data analysis was done with statistical package for the social sciences (SPSS) version 20.0. Percentages, means and standard deviations (SD) were calculated. For analytical purpose Chi-square test was used to measure the significance. Results: The study population consisted of 24 (60%) males and 16 (40%) females. The mean of the years of experience was 10.5 years (SD=5.5). 47.5% of the study population agreed that they worked up to 8 hours and 12 hours per day. 57.5% reported of finding work from home more stressful due to increase in responsibilities of household as well as child care. 87.5% developed moderate stress and 47.5% experienced moderate burnout due to personal issues. Conclusions: To conclude, the prevalence of stress due to work from home situation was much higher than burnout among the IT professionals. Although they had the perks of reduction in travel time, the other responsibilities of increased domestic workload caused considerable stress.